2016
DOI: 10.1136/heartjnl-2015-308826
|View full text |Cite
|
Sign up to set email alerts
|

TrimethylamineN-oxide and prognosis in acute heart failure

Abstract: Objective Acute heart failure (AHF) is associated with high mortality and morbidity. Trimethylamine N-oxide (TMAO), a gut-derived metabolite, has reported association with mortality risk in chronic HF but this association in AHF is still unknown. The present study investigated TMAO in patients admitted to hospital with AHF, and association of circulating levels with prognosis. Methods In total, 972 plasma samples were analysed for TMAO concentration by liquid chromatography-mass spectrometry. Associations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
196
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 208 publications
(211 citation statements)
references
References 28 publications
13
196
0
2
Order By: Relevance
“…Collectively, with beneficial prognostic information available for heart failure, [17,18] chronic kidney disease [19,20] and now acute MI, TMAO is proving to be an applicable biomarker across a range of cardio-renal pathological states.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, with beneficial prognostic information available for heart failure, [17,18] chronic kidney disease [19,20] and now acute MI, TMAO is proving to be an applicable biomarker across a range of cardio-renal pathological states.…”
Section: Discussionmentioning
confidence: 99%
“…However, a functional relevance of an impaired and/or altered bacterial profile as a primary risk factor or early disease marker for the initial onset of heart failure seems to be conceivable as well. Of note, recent studies have shown that intestinal bacterial‐dependent generated trimethylamine‐N‐oxide (TMAO) levels in blood are a prognostic factor for long‐term mortality risk in HF patients independent of traditional risk factors and indices 43, 44. In our study we focused on HF patients mostly in an acute state of decompensation.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in metabolite profiles seem not to be disease specific, because similar differences were observed in serum samples of patients with diseases such as nonHodgkin lymphoma, congestive HF, and communityacquired pneumonia (CAP) [182]. In separate studies, the levels of the metabolite, trimethylamine N-oxide (TMAO), were shown to be associated with the outcome in both acute HF and CAP patients [183,184]. This is not surprising because systemic metabolic dysfunction is a general process that can be observed in other diseases.…”
Section: Metabolitesmentioning
confidence: 99%